Incidence of gastroenteritis in Norway--a population-based survey. - Kuusi, M. (Cambridge University Press, 2003)
In 1999-2000 we conducted a one-year, retrospective population-based survey in Norway to estimate the incidence of gastroenteritis and study the association with selected exposures. A self-administered questionnaire was mailed to 3000 persons selected at random from the population registry, with 250 persons being contacted each month. The response rate was 61%. The incidence of acute gastroenteritis was 1.2 per person-year. The incidence was higher for women than for men. Of the total of 171 cases, 29 (17%) consulted a physician, 13 (8%) reported that a stool sample was taken, and 7 (4%) were admitted to hospital. Among children aged less than 15 years, drinking water from a private water supply was associated with illness, while using chlorinated water was protective. Among adults aged 20-40 years, travelling abroad was associated with illness. The incidence in our survey is similar to rates found by FoodNet in United States.